A comparative evaluation of the sealing ability of two calcium silicate based sealers and a resin epoxy-based sealer through scanning electron microscopy and bond strength - mai abd el rahman; Mohamed Y. Hassan (Universidade Estadual de Campinas, 2021)
Aim: this study aimed to compare the sealing ability of two types of commercially available calcium silicate bioceramic based root canal sealers and a resin based root canal sealer. Methods: Twenty one single-rooted teeth were used, samples (n= 21) were randomly divided into three groups according to the sealer used (group A; ADSEAL, group B; Wellroot, group C; Ceraseal). Roots were then cleaved longitudinally in the labiolingual direction; all samples were then sectioned at three, six, and nine mm from the root tip. The penetration of sealers into the dentinal tubules was examined at 1000x with a scanning electron microscope. Data were tested for normality using Shapiro Wilk test. ANOVA test was used for analyzing normally distributed data followed by Bonferroni post hoc test for pair-wise comparison. Significance level p≤0.001. Results: groups B and C showed better sealing ability than group A in all the three sections. The coronal section showed higher sealing ability than the middle section followed by the apical section in the three tested groups. Conclusion: it can be concluded that both calcium silicate-based sealers had better sealing ability and higher bond strength than the resin epoxy- based sealer.